2018
DOI: 10.1007/s12035-018-1311-6
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Factor Domain-Mediated Delivery of Nurr1 Transcription Factor Enhances Tyrosine Hydroxylase Activity and Protects from Neurotoxin-Induced Degeneration of Dopaminergic Cells

Abstract: The orphan transcription factor nuclear receptor-related 1 protein (Nurr1, also known as NR4A2) plays a key role in embryonic development and maintenance of mesencephalic dopaminergic neurons in the substantia nigra. Nurr1 deficiency is associated with Parkinson's disease where dopaminergic neurons degenerate suggesting that counter-regulation of Nurr1 activity may have therapeutic effects. Here, we bacterially expressed and isolated a human Nurr1 fusion protein containing a N-terminal cell delivery domain der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Consistent with this, recent studies have shown that the number of neurons expressing tyrosine hydroxylase (TH), the DAsynthesizing enzyme, increases in the adult mouse substantia nigra compacta in response to photoperiod (28) and in the VTA following deep brain stimulation (29), social defeat (30), and chronic exposure to methamphetamine (31). Given that the transcription factor Nurr1 (32) is involved in the acquisition (33) and maintenance (34) of the DAergic phenotype (35), and that its expression is activity dependent (36,37), we investigated whether Nurr1 and TH expression are affected by nicotine-mediated circuit activation during development.…”
mentioning
confidence: 87%
“…Consistent with this, recent studies have shown that the number of neurons expressing tyrosine hydroxylase (TH), the DAsynthesizing enzyme, increases in the adult mouse substantia nigra compacta in response to photoperiod (28) and in the VTA following deep brain stimulation (29), social defeat (30), and chronic exposure to methamphetamine (31). Given that the transcription factor Nurr1 (32) is involved in the acquisition (33) and maintenance (34) of the DAergic phenotype (35), and that its expression is activity dependent (36,37), we investigated whether Nurr1 and TH expression are affected by nicotine-mediated circuit activation during development.…”
mentioning
confidence: 87%
“…Although various differentiation protocols were described for generating mDA neurons, we believe that only viral transduction-free and cDNA transfection-free approaches are worthy of consideration for cells in replacement therapies. Besides the small molecules and the cytokines used in this study, cell penetrating peptides of recombinant transcription factors [56,57] or in situ transdifferentiation of astrocytes [58,59,60] avoid negative side effects, consequently being eligible for PD therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A second strong behavioral response was found upon downregulation of the fly ARG-TF Hr38, a homolog of the human Nurr1/NR4A2 ARG, whose continued transcription is required for maintenance of adult mammalian dopaminergic neurons (DANs) [33]. Moreover, increasing Nurr1 expression helps generate DANs from iPSCs [34], while the expression of a nuclear-targeted Nurr1 fragment in dopaminergic SH-SY5Y cells increased tyrosine hydroxylase expression and protected cells from the DAN-specific neurotoxin 6-hydroxydopamine [35]. Nurr1 expression is reduced in some cases of PD, and the authors speculate that protein expression of fragments of Nurr1 may alleviate PD neurodegeneration [35].…”
Section: Hr38/nurr1/nr4a2mentioning
confidence: 99%
“…Moreover, increasing Nurr1 expression helps generate DANs from iPSCs [34], while the expression of a nuclear-targeted Nurr1 fragment in dopaminergic SH-SY5Y cells increased tyrosine hydroxylase expression and protected cells from the DAN-specific neurotoxin 6-hydroxydopamine [35]. Nurr1 expression is reduced in some cases of PD, and the authors speculate that protein expression of fragments of Nurr1 may alleviate PD neurodegeneration [35]. Furthermore, HDAC inhibitors increase dopamine aminotransferase (DAT) expression in DANs via acetylation of Nurr1 promoters and increased Nurr1 transcription [59].…”
Section: Hr38/nurr1/nr4a2mentioning
confidence: 99%